Dermatitis Kontak Alergi - Ramadhina Ramadhina; Malahayati Malahayati (Pusat Riset dan Inovasi Nasional, 2026)
Allergic contact dermatitis (ACD) is an inflammatory skin process caused by specific allergens. ACD is classified as Type IV hypersensitivity, which is sensitive to allergens. A 57-year-old woman presented to the Dermatology and Venereology Clinic at Malahayati General Hospital in Bireun with complaints of red patches on her right and left legs and on her right and left elbows for approximately two months. According to the patient, the red patches initially appeared as circular patches with white scales the size of a coin on the elbows, accompanied by itching, which then spread. The itching worsened when the patient sweated, causing her to scratch, which enlarged the lesions and caused red wounds. The skin on the lesions tended to be dry with active edges and a calmer center. The itching improved after bathing. The patient is a housewife. The patient also said that she sweats frequently. According to the patient, the itching is not affected by the food she consumes every day. The patient was given steroid pharmacotherapy, namely 1% hydrocortisone cream, 0.1% mometasone furoate cream, and 10 mg cetirizine tablets once daily.